Treniranje mladih košarkarjev - Beranič, Lovro (Šport (Ljubljana), 2019)
In the process of developing the young basketball players, it is a series of factors that condition biological growth and changes in the morphological structure and constitution of the body, as well as factors that develop basic physical and functional abilities and also have influence to technique and tactics of the game. Optimal programming of basketball training means that we also should know the main developmental characteristics of young players before puberty, during puberty and after puberty. We also need to know the interaction of all factors that should influence to the success of basketball.
Keywords: basketball; developmental characteristics; košarka; mladi igralci; razvojne značilnosti; sport; šport; training; trening; young player